DOI: 10.14264/uql.2016.107
|View full text |Cite
|
Sign up to set email alerts
|

Selenium and oxidative stress modulation during extracorporeal circulation

Abstract: Oxidative stress occurs when there is an imbalance between reactive oxygen and nitrogen species (RNOS) and the antioxidant system. In cardiac surgery patients and the critically ill there is an association between oxidative stress and morbidity and mortality.Extracorporeal circulation (ECC) encompasses cardiopulmonary bypass (CPB) which is used for cardiac surgery; extracorporeal membrane oxygenation (ECMO) which is used for cardio-respiratory support in the critically ill and haemodialysis which is used in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 233 publications
(358 reference statements)
0
1
0
Order By: Relevance
“…Also, selenium deficiency may be involved in the development and progression of CVDs, possibly by 1-increasing thromboxane B2 synthesis, which subsequently leads to platelet aggregation and 2-decreasing prostacyclin production, which inhibits platelet aggregation (12). The level of selenium dramatically declines following heart surgeries and dialysis (13), resulting in unwanted complications and morbidities in both conditions (14,15). A previous study also indicated a reduction in selenium level in patients under CABG surgery (14).…”
Section: Introductionmentioning
confidence: 99%
“…Also, selenium deficiency may be involved in the development and progression of CVDs, possibly by 1-increasing thromboxane B2 synthesis, which subsequently leads to platelet aggregation and 2-decreasing prostacyclin production, which inhibits platelet aggregation (12). The level of selenium dramatically declines following heart surgeries and dialysis (13), resulting in unwanted complications and morbidities in both conditions (14,15). A previous study also indicated a reduction in selenium level in patients under CABG surgery (14).…”
Section: Introductionmentioning
confidence: 99%